A ESTÉTICA DO AMOR EM ADÉLIA E SALOMÃO - Vânia Cristina Alexandrino Bernardo (Universidade do Oeste Paulista, 2007)
Abstract: This work is resulted of the some discoveries of biblical words in Adélia Prado's poetry. It's a reflection on a common point between these texts: the love. It is an attempt of conjugating the biblical verbs beside adeliano's subjects. In fact, most of the characters walked in the old Canaã of Jesus' times. In Adelia's poetic space, they point us a road: Bible by the road of the lyricism. It is the advisable itinerary direction for readers that desire to nourish his soul's eyes with pictures that surpass people's understanding and satisfy the spirit of poetry.